Teacher Professionalism in the 21st Century: Challenges, Roles, and Enhancement Efforts - Muhammad Dinul Adha; Zulkifli Musthan (Southeast Asian Journal of Global Trends and Issues in Education, 2026)
Background: Teacher professionalism is a fundamental factor in improving the quality of education in the 21st century. Technological advancements, the implementation of the Merdeka Curriculum, the diverse characteristics of learners, and increasing global competency demands require teachers to continuously improve their competence and adaptability. Objective: This study aims to analyze the challenges of teacher professionalism in the 21st century, identify the strategic roles of teachers, and examine various efforts to enhance teacher professionalism. Method: The study uses a descriptive qualitative approach through a documentation study of scientific articles, books, policy documents, and relevant publications. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. Results: The study identifies five main challenges to teacher professionalism, namely curriculum changes, digital transformation, learner diversity, administrative burdens, and wellbeing. Furthermore, enhancing teacher professionalism requires continuous professional development, learning communities, technology based administrative simplification, and increased wellbeing. Conclusion: Enhancing teacher professionalism requires a comprehensive, collaborative, and sustainable approach to meet the demands of 21st century education. Contribution: This study offers an analytical framework that integrates challenges, role transformations, and strategies for enhancing teacher professionalism as a basis for policy development, educational practices, and future research.